Gene lrrk2 e seu papel no controle do consumo compulsivo de etanol: da abordagem transcritômica ao isolamento de um gene candidato - Daniel Almeida da Silva e Silva (2016)
Alcohol compulsive drinking despite serious adverse medical, social and economic consequences is a characteristic of alcohol use disorders (AUD). Alcohol is the most commonly used addictive substance, and has its admitted use and even encouraged. Over the past 20 years, this disorder has raised from eighth to fifth leading risk factor for premature death and disability in the world's population, accounting for 2.5 million deaths worldwide in 2010. Clinically, an occasional and controlled drug consumption is distinct from addiction. The progression from controlled consumption to loss of control or compulsion is influenced by many factors, including the drug itself, psychological factors and environmental and genetic factors. In order to try to elucidate the genetic factors that can drive or contribute to development of compulsive behavior and uncontrolled alcohol intake, it was evaluated the transcriptome of the striatal region in a murine model of chronic consumption and free choice ethanol. In this model, after 16 weeks of chronic ethanol intake, the animals were divided into three groups according to their drug use profile: "Light group" (preference for water throughout the experiment); "Heavy Group" (preference for ethanol, but significantly intake reduction when the drug is taste-adulterated by quinine); "Inflexible Group" (preference for ethanol and overconsumption, even after the taste-adulteration). Assessed by microarray assay, the global transcription levels of these animals were compared in a so-called striatum region of the brain, which is involved in the positive reinforcement and habit-forming mechanisms, processes directly affected during the progression of the disease. Through the expression analysis, it was found that the LRRK2 in neurons in Parkinson's disease pathway is deregulated between the different groups, and among all genes in this pathway, the Lrrk2 gene was the only gene found hyper-regulated just in those inflexible animals. This gene is responsible for controlling neuronal processes such as reuptake of synaptic proteins, synaptic plasticity and development of dendritic spines. In comparison with the wild-type animals, the functional validation of this gene showed that knockout animals for the Lrrk2 gene have an enhanced preference to and ethanol consumption, an increased motivation to the drug seeking and taking, an inflexible or compulsive ethanol consumption, an enhanced basal state of anxiety and a decreased sensitivity to the sedative effects of ethanol. Together, these data support the Lrrk2 gene as an important molecular substrate responsible for the consolidation of compulsive and uncontrolled ethanol consumption.